On the limiting equilibrium state of a nonlinear anisotropic body with a crack - Kaminsky, A. A.; Kurchakov, E. E. (Reports of the National Academy of Sciences of Ukraine, 2015)
The limiting equilibrium state of a nonlinear anisotropic body with a mode I crack in the presence of a prefracture zone is studied. By the numerical solving of the associated boundary-value problem, it is established how the crack length influences the displacement and deformation fields. Features of these fields in vicinities of the crack and the prefracture zone are revealed.